2020
DOI: 10.1002/acr2.11110
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: State‐Level Number of Physically Inactive US Adults With Arthritis Who can Improve Their Anxiety and Depression by Exercising

Abstract: Objective. Provide state-level estimates of the number of physically inactive adults in the United States with arthritis and other rheumatic and musculoskeletal diseases (RMDs) who could improve their anxiety and depression by exercising.Methods. Utilizing 1) number-needed-to treat (NNT) data from two prior meta-analyses of randomized controlled trials addressing the effects of exercise on anxiety and depression in adults with arthritis and other RMDs, 2) recent state-level prevalence estimates on arthritis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For example, a previous systematic review with meta-analysis reported that the NNT for adults with chronic musculoskeletal pain treated with topical nonsteroidal antiinflammatory drugs (NSAIDs) was 5 for 1 (20%) to benefit (7). When using standardized mean difference effect sizes to calculate the NNT, the larger the effect size, the smaller the NNT and the potential for a greater number of participants to benefit (8). Details regarding the approach we used are available elsewhere (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a previous systematic review with meta-analysis reported that the NNT for adults with chronic musculoskeletal pain treated with topical nonsteroidal antiinflammatory drugs (NSAIDs) was 5 for 1 (20%) to benefit (7). When using standardized mean difference effect sizes to calculate the NNT, the larger the effect size, the smaller the NNT and the potential for a greater number of participants to benefit (8). Details regarding the approach we used are available elsewhere (8).…”
Section: Methodsmentioning
confidence: 99%
“…When using standardized mean difference effect sizes to calculate the NNT, the larger the effect size, the smaller the NNT and the potential for a greater number of participants to benefit (8). Details regarding the approach we used are available elsewhere (8).…”
Section: Methodsmentioning
confidence: 99%